Theoretical explorations of structure, mechanical properties, fracture toughness, electronic properties, and thermal conductivity of Ag-doped η′-Cu6Sn5. (February 2022) - Yang, Ancang; Duan, Yonghua; Li, Caiju; Yi, Jianhong; Peng, Mingjun
Abstract: In this work, the phase stability, elasticity, fracture toughness, electronic characteristics and thermal conductivity of Ag-doped η′-Cu6 Sn5 were explored based on the first-principles calculations. Herein, four Cu doping sites and three Sn doping sites were considered based on the crystal structure of η′-Cu6 Sn5 . The calculated results show that the doping of Ag can enhance the stability, change the elastic properties, and increase the ductility of η′-Cu6 Sn5 . Moreover, Ag doping changes the elastic anisotropy in different directions. Besides, Ag doping improves the fracture toughness and thermal conductivity of η′-Cu6 Sn5, and enhances the strength of covalent bonds in the structure. Graphical abstract: Image 1 Highlights: The results show that both η′-Cu6 Sn5 and doping systems are thermodynamically and kinetically stable. The doping of Ag can enhance the stability, change the elastic properties, and increase the ductility of η′-Cu6 Sn5 . Ag doping changes the elastic anisotropy in different directions. Ag doping improves the fracture toughness and thermal conductivity of η′-Cu6 Sn5 .